Model-Based Approach for Lateral Maneuvers of Bird-Size Ornithopter. - Sánchez-Laulhe Cazorla, Ernesto; Satué Crespo, Álvaro César; Nekoo, Saeed Rafee; Ollero, Anibal (My University, 2024)
A model-based approach for lateral maneuvering of flapping wing UAVs in closed spaces is presented. Bird-size ornithopters do not have asymmetric actuation in the wing due to mechanical complexity, so they rely upon the tail for lateral maneuvering. The prototype E-Flap can deflect the vertical tail to make maneuvers out of the longitudinal plane. This work defines simplified equations for the steady turning maneuver based on the body roll angle. The relation between the velocity of the prototype and the turning radius is also stated. Then, an approach to the attitude is proposed, defining the relation between the deflection of the vertical tail and the roll angle. We prove that, even though this deflection causes a yaw moment, the coupling between yaw and roll dynamics generates also a roll rate. To validate this simplified model, a simple control is presented for continuous circular trajectory tracking inside an indoor flight zone. The objective is to track circular trajectories of a radius 2 times greater than the wingspan at a constant height. Results show a very good agreement between the theoretical and experimental turning radius. In addition, the direct relation between the vertical tail deflection and the roll rate of the ornithopter is identified. Even though the desired radius is not reached, the FWUAV is capable of maintaining a closed turning maneuver for several laps. Therefore, the insight provided by the model proves to be an appropriate approach for aggressive lateral maneuvers of bird-size ornithopters.
Keywords: Aerodinámica; Aviones - Modelos; Flapping-wing; Circular flight; Ornithopter; Dynamics